Identificação de anomalias térmicas por sensoriamento remoto em Cuiabá/MT - Silva, Pablinne Cynthia Batista da Silva e (2016)
The large agglomerates of urban areas end up creating a new own climate through the replacement of native vegetation with artificial surfaces, among others. The impacts caused by human action on the environment in Cuiabá / MT were responsible for changes in the ground cover, and consequently the climatic variations, leading to formation of thermal anomalies. Remote sensing is an alternative and effective tool for monitoring the urban climate, providing information of spatio-temporal environment. The aim of this study was to identify thermal anomalies and their spatio-temporal relationship with the different ground cover by remote sensing in Cuiabá/MT 1985 to 2011. The surface temperature showed significant temporal variation resulting from rapid urban growth witnessed in years. The replacement of vegetated areas for anthropic areas negatively affects the heat balance of the surface. Predominantly were identified thermal anomalies in the north and east of the city, caused by the increase in built and urban fabric areas. The mapping of ground cover with the surface temperature estimates are adequate for spatial and temporal assessment of the different biophysical parameters. The parameters discussed in this study are of prime importance to assess the impacts of urbanization. In view of this, the analysis of the effects of ground cover of urban microclimate pointing thermal anomalies indicated for remote sensing is adequate to urban microclimates studies contributing to the decision making regarding the planning of urban spaces.